Milk-derived proteins and peptides in clinical trials - Artym, Jolanta; Zimecki, Michał (Postȩpy higieny i medycyny doświadczalnej, 2013)
Clinical trials are reviewed, involving proteins and peptides derived from milk (predominantly bovine), with the exception of lactoferrin, which will be the subject of another article. The most explored milk fraction is α-lactalbumin (LA), which is often applied with glycomacropeptide (GMP) - a casein degradation product. These milk constituents are used in health-promoting infant and adult formulae as well as in a modified form (HAMLET) to treat cancer. Lactoperoxidase (LCP) is used as an additive to mouth hygiene products and as a salivary substitute. Casein derivatives are applied, in addition, in the dry mouth syndrome. On the other hand, casein hydrolysates, containing active tripeptides, found application in hypertension and in type 2 diabetes. Lysozyme is routinely used for food conservation and in pharmaceutical products. It was successfully used in premature infants with concomitant diseases to improve health parameters. When used as prophylaxis in patients with scheduled surgery, it significantly reduced the incidence of hepatitis resulting from blood transfusion. Lysozyme was also used in infected children as an antimicrobial agent showing synergistic effects in combination with different antibiotics. Proline-rich polypeptide (PRP) was introduced to therapy of Alzheimer's disease patients. The therapeutic value of PRP was proved in several clinical trials and supported by studies on its mechanism of action. Concentrated immunoglobulin preparations from colostrum and milk of hyperimmunized cows showed efficacy in prevention of infections by bacteria, viruses and protozoa. A nutrition formula with milk-derived TGF-β2 (Modulen IBD®) found application in treatment of pediatric Crohn's disease. In conclusion, the preparations containing milk-derived products are safe and effective measures in prevention and treatment of infections as well as autoimmune and neoplastic diseases.